Data Collection in Maine: Assessing the Return on Public Investment in Maine’s Early Childhood System - Reidt-Parker, Judy (Maine Policy Review, 2009)
To better understand the outcomes of investments in early childhood, we need comprehensive data to measure benchmarks, according to Judy Reidt-Parker. She describes the current state of data collection in Maine and discusses data that are needed and where there are opportunities for improvement. The greatest need is for the development of a common set of child and program outcomes that can be shared across departments and systems and for linking systems so that children’s progress can be followed longitudinally